Versatility of nasolabial flaps for the management of severe trismus in oral submucous fibrosis - S M Balaji (Wolters Kluwer Medknow Publications, 2016)
Background: Oral submucous fibrosis (OSMF) is a chronic insidious disease affecting any part of the oral cavity and sometimes the pharynx. It is a collagen-related disorder predominantly associated with tobacco/areca nut chewing habit and characterized by progressive hyalinization of the submucosa. Prevalence of OSMF is 2.01%, and malignant transformation rate of 2.3%-7.6% has been reported in the literature. Measures such as forcing the mouth open and cutting the fibrotic bands have resulted in more fibrosis and disability. Aim: Various surgical treatment modalities have been advocated in the surgical management of OSMF with variable results. This retrospective study evaluates the efficacy of nasolabial flap in the surgical treatment of OSMF. Materials and Methods: Retrospective analysis of 42 patients who underwent surgical management of OSMF with mouth opening <20 mm by nasolabial flap at authors center from 2000 to 2015. Only the cases diagnosed as advanced OSMF based on long-standing positive history of habits (chewing tobacco, betel nut, etc.), clinical and histopathological examination. OSMF due to other causes such as nutritional deficiency, immunological diseases, and systemic illness with medically compromised patients were excluded from the study. Inferiorly based nasolabial flaps were raised in the supramuscular plane and transferred intraorally through a transbuccal tunnel. Results: The study groups consist of 42 cases of clinical and histopathologically proven cases of OSMF treated by nasolabial flap. Out of 42 cases, 39 (92.85%) were males and 3 (7.15%) were females which showed a male predominance and the ratio was 13:1. The mean (standard deviation [SD]) preoperative mouth opening was 14.60 mm (3.06). After release of fibrotic bands, a mean forced intraoperative mouth opening of 36.27 (2.11) mm was achieved. The mean (SD) postoperative mouth opening was 33.05 mm (2.40) at the end of 2-year follow-up. The mean (SD) increase in mouth opening after surgical management at the end of 2-year follow-up is 18.46 mm (1.89). Sixteen out of 42 patients' histopathological report turned out to be dysplastic. The mean (SD) follow-up was 2.79 years (1.08). There was no incidence of infection in the transferred flap and the recipient site in all cases except one case with malignant transformation. All flaps healed without evidence of infection, dehiscence, or necrosis. Results were assessed by comparing the pre- and post-operative maximum mouth opening. Conclusion: The nasolabial flap is a versatile flap, which can be successfully used in the reconstruction of defects created after the release of fibrotic bands in OSMF. The versatility of the nasolabial flap has been attributed to its reliable vascularity derived from numerous vessels in the vicinity. Major advantage is the ease of elevation, proximity to the defect, suitable size for coverage of defect, minimal swallowing and speech difficulties, and a relatively cosmetic result as scar is in natural crease. All the cases treated for OSMF using bilateral nasolabial flaps showed adequate mouth opening at 2-year follow-up postoperatively, recommending its use.